Applied Thermodynamics of Fluids. - Goodman, Anthony; Sengers, J. V.; Peters, Cor J. (Royal Society of Chemistry, The Ingram Publisher Services [distributor], 2010)
Annotation Published under the auspices of both IUPAC and its affiliated body, the International Association of Chemical Thermodynamics (IACT), this book will serve as a guide to scientists or technicians who use equations of state for fluids. Concentrating on the application of theory, the practical use of each type of equation is discussed and the strengths and weaknesses of each are addressed. It includes material on the equations of state for chemically reacting and non-equilibrium fluids which have undergone significant developments and brings up to date the equations of state for fluids and fluid mixtures. Applied Thermodynamics of Fluids addresses the needs of practitioners within academia, government and industry by assembling an international team of distinguished experts to provide each chapter. The topics presented in the book are important to the energy business, particularly the hydrocarbon economy and the development of new power sources and are also significant for the application of liquid crystals and ionic liquids to commercial products. This reference will be useful for post graduate researchers in the fields of chemical engineering, mechanical engineering, chemistry and physics.
Keywords: Fluids -- Thermal properties.; elektronické knihy; electronic books